"Let us vote!" : youth voting rights and the 26th amendment - Frost, Jennifer, 1961- (NYU Press, 2021)
""Let Us Vote" tells the story of the multifaceted endeavor to achieve youth voting rights in the United States. Over a thirty-year period from World War II to the early 1970s, Americans, old and young, Democrat and Republican, in politics and culture built a movement and momentum for the 26th Amendment to the US Constitution. This amendment gave the right to vote to 18, 19, and 20-year olds in 1971, and it was the last time that the United States significantly expanded voting rights. The 26th Amendment means a major expansion of American democracy came right end of "the sixties." Progress toward achieving youth suffrage built on the decade's many developments, most importantly the movement and legislation for African-American civil and voting rights. This story illuminates the process of achieving political change, with the convergence of "top-down" initiative and "bottom-up" mobilization, coalition-building, multiple arguments, and strategic flexibility leading to success. Supporters came from a broad, bipartisan group of Americans and achieved a constitutional amendment that benefited every constituency in the nation. With the 50th anniversary of this important constitutional amendment this year [2021], and as calls for lowering the voting age to sixteen multiply today within the context of climate crisis, gun violence, and police brutality-all of which affect young people disproportionately-the 26th Amendment deserves our attention, application, and appreciation"-- Provided by publisher.
Keywords: Voting -- United States.; Youth -- Political activity -- United States.; Voting age -- United States.; Political culture -- United States.; United States -- Politics and government.; Vote -- États-Unis.; Jeunesse -- Activité politique -- États-Unis.; Âge de voter -- États-Unis.; États-Unis -- Politique et gouvernement.; HISTORY / United States / 20th Century; Political culture; Politics and government; Voting; Voting age; Youth -- Political activity; United States